Analisis Pengaruh Iklim Kerja dan Beban Kerja Fisik Terhadap Kejadian Hipertensi pada Pekerja Plat Baja PT Gunawan Dianjaya Steel Tbk. - Vina Rohmatul Ummah; Zufra Inayah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2025)
10 - 20% of hypertension triggers come from the work environment, including the work climate and physical workload which affects physiological reactions when the body is unable to maintain its capacity due to increased strain on blood flow. The results of the MCU of PT GDS Tbk. experienced an increase of 42% hypertension in 2022, 22% increase from production area steel plate workers, based on initial observations of steel plate workers there were 60% suffering from hypertension and 40% normal blood pressure. The study aims to analyze the effect of work climate and physical workload on the incidence of hypertension in steel plate workers of PT Gunawan Dianjaya Steel Tbk. This type of quantitative research is observational analytics with cross-sectional design. Sampling using purposive sampling amounted to 76 production workers. Data analysis using logistic regression test, obtained 75% of steel plate workers work not according to TLV, 72.4% of workers have moderate physical workload, and 67.1% of steel plate workers experience hypertension. Statistical test results p-value work climate 0.375, OR 0.488 (95% CI: 0.108 - 2.205), while p-value physical workload 0.003, OR 8.647 (95% CI 2.094 - 35.709). Work climate has no effect on hypertension, while physical workload affects hypertension in steel plate workers with a large effect of R = 0.197